Impact of Prior Vaccination History on Risk of Vaccine Failure with Live Attenuated and Inactivated Influenza Vaccines in Children, 2013–14 through 2015–16. (4th October 2017) - McLean, Huong Q; Caspard, Herve; Griffin, Marie R; Gaglani, Manjusha; Peters, Timothy R; Poehling, Katherine A; Ambrose, Christopher S; Belongia, Edward
Abstract: Background: Prior season vaccination may influence influenza vaccine effectiveness; however, little is known about the impact of prior vaccination or vaccine type received. We assessed prior vaccination history and risk of influenza in children over 3 seasons. Methods: Children aged 2–17 years seeking outpatient care for febrile acute respiratory illness were recruited during the 2013–14 through 2015–16 seasons (1 vaccine-mismatched H3N2 season and 2 H1N1pdm09 seasons) at 4 US sites. Influenza was confirmed by RT-PCR. Vaccination data for the season of enrollment (current) and 3 prior seasons were obtained from medical records and immunization registries. Among children who received 1 dose of influenza vaccine during the current season, risk of vaccine failure (ie, PCR-confirmed influenza) was estimated using test-negative design with logistic regression models adjusted for age, season, enrollment site, enrollment week (relative to peak), and outpatient visits. Risk of failure with live attenuated influenza vaccine (LAIV) and inactivated influenza vaccine (IIV) were modeled separately. Separate models were used for vaccine history based on number of seasons and vaccine type received (ie, none, LAIV, IIV, both). Results: Influenza was detected in 191 (12%) of 1601 children who received 1 vaccine dose during the current season: 117 H3N2 and 74 H1N1pdm09. Among 508 current season LAIV recipients, 239 (47%) received LAIV and 144 (28%) received IIV in the prior season. Among 1093 current season IIV recipients, 94 (9%) received LAIV and 711 (65%) received IIV in the prior season. For LAIV, receipt of vaccine (any type) in a prior season was associated with a decreased risk of H3N2 failure (odds ratio 0.23; 95% CI, 0.09–0.57). Prior vaccination was not associated with risk of LAIV vaccine failure against H1N1pdm09. For IIV, there was no evidence that prior vaccination was associated with risk of vaccine failure against H3N2 or H1N1pdm09. Similar results were seen in children without any high-risk conditions. Conclusion: Risk of vaccine failure among vaccinated children varied by vaccine type and virus subtype. Future studies should examine immunologic effects to better understand these differences. Disclosures: H. Q. McLean, MedImmune: Grant Investigator, Research support; H. Caspard, MedImmune: Employee, Salary; M. R. Griffin, MedImmune: Grant Investigator, Grant recipient; M. Gaglani, MedImmune: Investigator, Research support; T. R. Peters, MedImmune: Investigator, Research support; K. A. Poehling, MedImmune: Investigator, Research support; C. S. Ambrose, AstraZeneca: Employee, Salary; E. Belongia, MedImmune: Grant Investigator, Research support